Pengembangan lembaga pendidikan islam transformatif berorientasi kewirausahaan dalam perspektif global - Muh Ibnu Sholeh; Prim Masrokan Mutohar; Agus Eko Sujianto (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study examines the development of entrepreneurial-oriented transformational Islamic educational institutions from a global perspective to determine the best strategies to establish Islamic educational institutions capable of making an excellent contribution to society and the world. This study concentrates on establishing entrepreneurial-oriented Islamic educational institutions to develop successful entrepreneurs and empower communities by acquiring skills and knowledge during the learning process. The library research approach was employed in this study. Researchers research books, publications, and materials directly connected to establishing transformational Islamic educational institutions from an entrepreneurial standpoint globally. Data collecting through offline and online searches for sources such as books, journals, articles, reports, papers, other relevant information sources, and existing research. An interactive qualitative model was used to examine the data from the literature review. This data analysis paradigm includes data collection, reduction, display, and conclusion drafting. According to the findings of this study, numerous factors must be addressed in the creation of transformational Islamic educational institutions from an entrepreneurial standpoint: improving teaching and research quality, extend the institution's reach and reputation, providing study programs and curricula that address global demands, develop pupils' creative and imaginative skills, establish a network with industry and businesses, and increase international collaboration.